Effect of intermittent compared with continuous light on testicular growth and histology of broiler chickens reared under high temperature - AL-HASSAN, D H; AL-KHAFAJI, SUAD KH; A ABDULKAREEM, TALAL (The Indian Journal of Animal Sciences, 2013)
The influence ofintermittent (IL) compared to continuous light (CL) on testicular growth and histology of birds reared under high temperature (30-35Â°C) was studied. Absolute or relative testicular weight were not affected by lighting treatment Numbers of spermatocyte, spermatid, sperm and total spermatogenic cells were greater (P